2014
DOI: 10.1515/ljss-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Motives Between Participants in Individual Sports Compared to Team Sports?

Abstract: The aim of this study was to explore which motives dominate among adolescents when it comes to participation in individual versus team sports. We expected that intrinsic motives will dominate in both groups. We also had a hypothesis that those who compete in individual sport will have higher scores on intrinsic and lower on extrinsic motivation than those in team sport. We also expected that intrinsic motives would explain why they had chosen individual sports instead of team sport. The participants were 78 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Satisfaction of psychological needs is positively correlated with identified and introjected regulation and intrinsic motivation [37,39,44]. In terms of competence satisfaction, introjected and identified regulations can positively predict strenuous exercise behavior, whereas external regulation is a more negative predictor of strenuous exercise behavior [45].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction of psychological needs is positively correlated with identified and introjected regulation and intrinsic motivation [37,39,44]. In terms of competence satisfaction, introjected and identified regulations can positively predict strenuous exercise behavior, whereas external regulation is a more negative predictor of strenuous exercise behavior [45].…”
Section: Introductionmentioning
confidence: 99%
“…The highest level of intrinsically motivated behavior includes activities people do only for enjoyment, pleasure, and fun and there are no rewards or discernible reinforcements involved [19,20]. Autonomous regulation is associated with action and maintenance of change for exercise [17,21], exercise-related selfesteem [22], greater physical fitness [23,24], more frequent self-reported exercise behavior [25], and more positive attitudes toward exercise [23,24]. Perceived autonomy support from friends is positively associated with identified regulation and intrinsic motivation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous regulation is associated with action and maintenance of change for exercise [17,21], exercise-related selfesteem [22], greater physical fitness [23,24], more frequent self-reported exercise behavior [25], and more positive attitudes toward exercise [23,24]. Perceived autonomy support from friends is positively associated with identified regulation and intrinsic motivation [25]. It has also been reported that perceived autonomy support from exercise instructors positively predicts relatedness, autonomy, competence need satisfaction, and intrinsic motivation [17].…”
Section: Introductionmentioning
confidence: 99%
“…The items represent five subscales: Interest/Enjoyment, Competence, Appearance, Fitness and Social. The two subscales Interest/Enjoyment and Competence reflect intrinsic motivation and regulation, and the other three reflect varying levels of extrinsic motivation and regulation (Jakobsen, 2014;Ryan et al, 1997). The validity and reliability of the MPAM-R have been addressed in previous research, where it has been demonstrated that the 30 items were clearly structured into a three-factorial order (amotivation, extrinsic and intrinsic motivation), and that the internal consistency measures for each subscale achieved Cronbach's alpha scores above .80 Ryan, 1993, in Ryan et al, 1997).…”
Section: Questionnaires and Their Validity And Reliabilitymentioning
confidence: 99%